A view of Émile Benoit’s house - Merrigan, Shirley (1988)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiante en folklore à l'université Memorial: « Folklore/French 4400: Fieldtrip to Black Duck Brook March 12-16 1988: A Report ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Folklore/French 4400: Fieldtrip to Black Duck Brook March 12-16 1988: A Report".